2021
DOI: 10.1038/s41598-021-99546-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental spatial heterogeneity of the impacts of COVID-19 on the top-20 metropolitan cities of Asia-Pacific

Abstract: This study investigated the environmental spatial heterogeneity of novel coronavirus (COVID-19) and spatial and temporal changes among the top-20 metropolitan cities of the Asia-Pacific. Remote sensing-based assessment is performed to analyze before and during the lockdown amid COVID-19 lockdown in the cities. Air pollution and mobility data of each city (Bangkok, Beijing, Busan, Dhaka, Delhi, Ho Chi Minh, Hong Kong, Karachi, Mumbai, Seoul, Shanghai, Singapore, Tokyo, Wuhan, and few others) have been collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…The emergence of the COVID-19 pandemic has resulted in positive environmental benefits due to restrictions on various industrial activities and transportation [ 9 ]. The reduction of environmental pollutants prompted a more pleasant outdoor environment [ 8 , 10 , 11 ]. In these circumstances, maintaining social distance and actively performing physical activity can provide reasonable health benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of the COVID-19 pandemic has resulted in positive environmental benefits due to restrictions on various industrial activities and transportation [ 9 ]. The reduction of environmental pollutants prompted a more pleasant outdoor environment [ 8 , 10 , 11 ]. In these circumstances, maintaining social distance and actively performing physical activity can provide reasonable health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Necessary methods such as social distancing and quarantine that limited physical activity and contact with numerous people, were implemented to prevent its spread [ 7 ]. It was under the influence of these limited activities that a reduced concentration of outdoor air pollutants was found [ 8 11 ]. Walking is a typical physical activity that can be performed in such a situation while maintaining social distance.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, corporate decision-makers have placed a greater premium on innovation as a means of ensuring a green environment (Xiaolong et al, 2021 ). GI was given special attention by researchers in marketing, the environment, business, and ethics (Ali G. et al, 2021 ). Green technologies would increase environmental sustainability while also assisting enterprises in gaining a competitive advantage (Tu and Wu, 2021 ).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…The spatiotemporal variations in aerosols could better reflect their own temporal and spatial variation laws and changes in human activities [11]. Based on data provided by the National Aeronautics and Space Administration (NASA) in 2019-2020, it was found that during the COVID-19 lockdown period, the AOD of all regions of the world decreased to some extent; for example, the AOD of the Ganges Plain in India declined by 30-40% compared with that of the same period in the previous year, and that of Poland decreased by 10%; similar trends also appeared in Spain, Italy, and other regions of China [12][13][14][15]. Saleem et al [16] predicted and supplemented the missing AOD value in Moderate-resolution Imaging Spectroradiometer (MODIS) using the extremely randomized trees model, and analyzed the relationship between four meteorological variables and AOD in Europe during the lockdown period from March to June 2020.…”
Section: Introductionmentioning
confidence: 99%